Energy systems design and operation : a unified method - Tostevin, G. Mark. ([S.l.] : McGraw-Hill Professional, 2012)
Best practices for the design and operation of energy systems Written by a global expert with 50 years of experience in the field, Energy Systems Design and Operation presents a formal, unified, and universal method for conceiving, designing, and operating the most appropriate energy system in any given situation. This authoritative guide describes how to express the scientific, technical, and economic parameters of an energy system in universal terms, and then reliably conduct its engineering and evaluation in those terms. The book also includes the algorithm and functional specification of the computer program for the unified method, application techniques, and software examples with source code. Learn how to: Develop a plan for adopting a unified method for energy systems Gather and process required information Formalize a procedure for the conversion, exchange, and storage of energy Extend the formal procedure to a unified method for the concept, design, and operation of energy systems Meet requirements for computing with a unified method Use and benefit from a unified method with real-world demonstrations of energy system operation and design Simulate and optimize energy systems with the unified method.
Keywords: Power (Mechanics); Power resources